Safety evaluation of arabinase (arabinan endo‐1, 5‐α‐L‐arabinanase) from Aspergillus tubingensis. Issue 1 (17th December 2019) - Okado, Nobuo; Sugi, Mai; Kasamoto, Sawako; Mizuhashi, Fukutaro; Roberts, Ashley; Danielewska‐Nikiel, Barbara; Sulaiman, Christina; Pham, Sa
Abstract: Arabinase is an enzyme recognized for its ability to degrade arabinan, a plant cell wall constituent. It has been applied in the food industry most commonly for juice processing. One commercial source of arabinase is Aspergillus tubingensis ( A. tubingensis ), a black Aspergillus  species. Given the intended use in food for human consumption, and noting its potential presence at trace levels in finished products, a series of safety studies including in vitro Ames and chromosome aberration assays, in vivo mammalian erythrocyte micronucleus and alkaline comet assays, and a 90‐day rat oral toxicity study were conducted. No test article‐related mutagenic activity was observed in the Ames assay. Although positive activity was observed in the chromosome aberration assay, this was not replicated in the in vivo genotoxicity assays including in preabsorptive cells. In the subchronic toxicity study, no test article‐related adverse effects were observed following oral administration of arabinase at doses of 15.3, 153, or 1, 530 mg total organic solids (TOS)/kg body weight/day to Sprague Dawley rats. The no‐observed‐adverse‐effect level was considered to be the highest dose tested (1, 530 mg TOS/kg body weight/day). The results of the genotoxicity studies and the subchronic toxicity study support the safe use of arabinase from A. tubingensis in food production. Abstract : A series of toxicological studies including in vitro and in vivo short‐term genotoxicity assays and a 90‐day subchronic oral toxicity study were conducted to evaluate the safety of arabinase from Aspergillus tubingensis . Arabinase was concluded to be nongenotoxic and was not associated with toxicity in rats at the highest dose tested (up to 1, 530 mg TOS/kg body weight/day). Study results provide reassurance of the safety of use of arabinase from A. tubingensis in food production.